1994
DOI: 10.1016/0014-5793(94)00928-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characterization of immunoreactive rat adrenomedullin in tissue and plasma

Abstract: Adrenomedullin is a new bioactive peptide recently isolated from pheochromocytoma. We report on the rat adrenomedullin distribution and molecular forms in various tissues and plasma. Using a sensitive radioimmunoassay system for rat adrenomedullin, high concentrations of immunoreactive rat adrenomedullin were detected in adrenal gland, lung and cardiac atrium. In lung and atrium, the immunoreactivity concentration in rat was about 610 times higher than that in human. The mean plasma concentration of immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 266 publications
(143 citation statements)
references
References 9 publications
2
140
0
1
Order By: Relevance
“…This finding was inconsistent with previous research in which a high concentration of immunoreactive ADM was found ubiquitously in all pulmonary tissue examined, including VSMCs and ECs, 6 and a high expression level of ADM mRNA was found in the lungs as well as in the adrenal glands. [7][8][9] This discrepancy can be explained by the possibility that ADM and ADT are synthesized by ECs and VSMCs as well, and that which is biosynthesized in the ECs is rapidly and continuously secreted into the blood or functions as an autocrine or paracrine regulator. 10 However, the ADM and ADT that is synthesized by VSMCs may be stored in the smooth muscle cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was inconsistent with previous research in which a high concentration of immunoreactive ADM was found ubiquitously in all pulmonary tissue examined, including VSMCs and ECs, 6 and a high expression level of ADM mRNA was found in the lungs as well as in the adrenal glands. [7][8][9] This discrepancy can be explained by the possibility that ADM and ADT are synthesized by ECs and VSMCs as well, and that which is biosynthesized in the ECs is rapidly and continuously secreted into the blood or functions as an autocrine or paracrine regulator. 10 However, the ADM and ADT that is synthesized by VSMCs may be stored in the smooth muscle cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies clarified that adrenomedullin is synthesized in various tissues, including vascular smooth muscles, glomerular mesangium, cardiac tissues and lungs [2,3,16]. Adrenomedullin has vasodilator and antiproliferative effects in vascular smooth muscle cells and mesangial cells [2,7].…”
Section: Hormonal Assaysmentioning
confidence: 99%
“…The plasma adrenomedullin increased dependent on the severity of diabetic nephropathy and retinopathy. Adrenomedullin has been found in various tissues, including vascular smooth muscles, kidneys, cardiac tissues and lungs [2,3]. Previous studies reported that the plasma concentration of adrenomedullin increases in patients with hypertension, renal failure and congestive heart failure [4,5], though the major source of circulating adrenomedullin is unknown.…”
mentioning
confidence: 99%
“…10 Immunoreactive AM has subsequently been detected in plasma and a variety of tissues, including blood vessels and lungs. 11,12 It has been reported that there are abundant binding sites for AM in the lungs. 13 We have shown that the plasma AM level increases in proportion to the severity of pulmonary hypertension and that circulating AM is partially metabolized in the lungs.…”
mentioning
confidence: 99%